PENGGUNAAN FORMALIN UNTUK PENGENDALIAN SAPROLEGNIASIS PADA TELUR IKAN NILA MERAH (Oreochromis sp.) - Sri Puji Astuti Wahyuningsih (The East Java Biological Society, 2006)
Saprolegniasis was a primary fungal disease that attacks fish eggs and fish. This disease was caused by Saprolegnia sp. The infections of Saprolegnia sp. in fish eggs can be minimized with dip treatment in formalin solution. This esearch was the control of saprolegniasis on red nila eggs (Oreochromis sp.) with formalin. This research used 400 red nila eggs. It was dipped suspension of Saprolegnia sp. (OD550 = 0,5) for 36 jam. The treatment was divided into four groups. Each group used 10 replication and each treatment with 10 eggs. The eggs in group 1 as control were not treated. The egg in-group 2, 3, and 4 were dipped formalin for five minute. The concentration of formalin in-group 2, 3, and 4 were 4 ml/L, 5 ml/L, and 6 ml/L. These data was taken after the treatment and the investigating parameter was the mean percentage of totally eggs that not infected by Saprolegnia sp. These data was analyzed by ANAVA and LSD at α = 5%. The results of this experiment showed that the increasing of formalin concentrations at each treatment caused significantly decreasing at the growth of Saprolegnia sp. on the red nila fish eggs. The control (1) group was not decreasing of the growth of Saprolegnia sp. The growth of Saprolegnia sp. in-group 2 decreased until 82%. The growth of Saprolegnia sp. in-group 3 decreased until 92%. The growth of Saprolegnia sp. in-group 4 decreased until 96%.